1981
DOI: 10.2307/2937325
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Concepts and Methodology for the Analysis of Animal Population Dynamics, with Particular Reference to Univoltine Species

Abstract: This paper presents some concepts and methodology essential for the analysis of population dynamics of univoltine species. Simple stochastic difference equations, comprised of endogenous and exogenous components, are introduced to provide a basic structure for density—dependent population processes. The endogenous component of a population process is modelled as a function of density in the past p generations, including the most recent. The exogenous component of the process consists of all density—independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 16 publications
2
128
0
Order By: Relevance
“…In keeping with predictions from unstructured population models (Royama 1981;Williams & Leibhold 1995;Jiang & Shao 2003), our simulations demonstrate that both negative and positive spurious DDD could arise in age-structured populations subjected to red environmental noise. We have also demonstrated that different densitydependent scenarios can lead to qualitatively different patterns of spurious DDD in age-structured populations.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In keeping with predictions from unstructured population models (Royama 1981;Williams & Leibhold 1995;Jiang & Shao 2003), our simulations demonstrate that both negative and positive spurious DDD could arise in age-structured populations subjected to red environmental noise. We have also demonstrated that different densitydependent scenarios can lead to qualitatively different patterns of spurious DDD in age-structured populations.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies on this topic have focused on unstructured models of homogenous populations (Royama 1981;Williams & Liebhold 1995;Jiang & Shao 2003), despite the fact that many organisms go through multiple stages during their life cycle or have spatially structured populations. We focus on age-structured populations here.…”
Section: Introductionmentioning
confidence: 99%
“…For the eastern budworm, the points represent generation survival in a single plot (plot G4), but for the western and jack pine budworms, they represent mean values for all the plot-years in OREG and the Michigan populations described in Foltz (1969), respectively. Because the author of figure 43B noted that "...the rise and fall of population density in...[plot G4] followed much the same pattern as...other areas...." (Royama 1984), and because he repeatedly used the numerical trend in this plot as an example (Royama 1981(Royama , 1984, I assume that this trend represents typical numerical behavior for the eastern budworm during an outbreak. As the outbreak progressed, S G systematically declined in both the eastern and western species.…”
Section: 639mentioning
confidence: 98%
“…More precisely, we assume these random deviations are additive on a log scale, a common assumption in population modeling and ecological time series analysis (e.g., Royama 1981;Turchin and Taylor 1992;Bjørnstad et al 1995;Ives et al 1999). Populations with identical traits can be expected to respond to environmental fluctuations in a similar way; that is, we expect a high-correlation r between their respective deviations from the deterministic growth rate.…”
Section: A Scenario For Competition-driven Sympatric Speciationmentioning
confidence: 99%